Effect of Polar and Nom-polar Aloe vera L. Leaf Extracts on α-amylase and α-Glucosidases Inhibitory Activity In vitro - H Fallah Huseini; B Asghari; J Asgarpanah; A Babai Zarch; T Eghbali Zarch (Journal of Medicinal Plants, 2013)
Background: Intestinal α-glucosidase and α-amylase are two carbohydrate-hydrolysing enzymes that play a key role in conversion of disaccharide to glucose. Inhibition of these two enzymes provides a therapeutic option for treatment of postprandial hyperglycemia in diabetic patients. Objective: The aim of the current study was to evaluate the inhibitory effects of different Aloe vera L. extracts against α-amylase and α-glucosidase in vitro. Methods: Aloe vera L. leaf was collected from the Institute of Medicinal Plants farm and several extracts were prepared by n-hexane, chloroform, ethyl acetate and methanol solvents. The inhibitory effects of the extracts were tested on α-amylase and α-glucosidase enzyme separately. In this experiment, the minimum concentration of the extract required for 50% inhibition of enzyme activity (IC50), was obtained and compared with acarbose as a positive control. Results: The results showed that total methanol extract of Aloe vera L. leaf had significantly (p<0.001) higher α-amylase inhibitory (28.2 ± 1.3 µg/ml) effect than other solvent fractions but lower than acarbose (25.4 ± 1.9 µg/ml). Furthermore total methanol extract and solvent fractions of methanol and ethyl acetate of Aloe vera L. leaf had significantly (p<0.001) higher inhibitory effect on α-glucosidase enzyme activity (2.3 ± 0.1 µg/ml, 2.7 ± 0.1 µg/ml, 3.4 ± 0.1 µg/ml, respectively) than other solvent fractions as well as compared with acarbose (5.8 ± 0.6 µg/ml). Conclusion: Total methanol extracts of Aloe vera L. leaf has strong α-amylase and α-glucosidase inhibitory activity than chloroform, n-hexane, chloroform, ethyl acetate and methanol solvent fraction.